Barley Yellow Dwarf Virus Confirmed in Argentine Bahiagrass in Northeastern Florida - Jacque Breman; James DeValerio; Amanda Gevens; Richard Cullen; W. Bird (EDIS)
PP-252, a 4-page illustrated fact sheet by J. Breman, J. DeValerio, A. Gevens, R. Cullen, and W. Bird, describes this viral disease of Argentine bahiagrass which has appeared in northeast Florida, the pathogen and hosts, symptoms, and disease management. Includes references. Published by the UF Department of Plant Pathology, April 2008.